Treatment Satisfaction With Couplelinks Online Intervention to Promote Dyadic Coping in Young Couples Affected by Breast Cancer - Fergus, Karen; Tanen, Adina; Ahmad, Saunia; Gardner, Sandra; Warner, Ellen; McLeod, Deborah; Stephen, Joanne; Carter, Wendy; Periera, Amanda (Frontiers in Psychology, 2022)
This study evaluated participant satisfaction with “Couplelinks,” an online psychological intervention designed for younger couples coping with breast cancer. The program included six experiential learning exercises (plus one optional module), psychoeducational information, and support from a personal mental health professional. The primary objectives were to examine participants’ perceptions of: the online intervention’s structure and content; the value of including an online facilitator; and benefits and drawbacks of the program. Post-treatment written questionnaires were completed by 26 patients and 27 male partners (N=53) following the intervention which occurred in the context of a randomized controlled trial. Participants reported an overall satisfaction rating of 4.3 out of 5 (SD=.54) and considered the facilitator’s role to be necessary 4.7 (SD=.60). The majority also found the program to be convenient 4.1 (SD=.81) despite some participants struggling to keep up with the modules. Qualitative thematic analysis of subjective data revealed participants valued the convenience and flexibility of the online intervention and appreciated the intervention’s involvement of both partners. Participants also reported that including a professional facilitator humanized the intervention, served as motivation to progress through the program, facilitated insight into their relationship, and was reassuring. Experiential gains noted by participants included that the program helped: (1) open channels of communication, (2) designate quality time for one another, (3) evoke feelings of unity and togetherness, and (4) inspire new insight in the relationship. Such feedback supports the feasibility and acceptability of the Couplelinks program while offering directions for improvement of online couple interventions in oncology.